Sponges as Emerging By-Product of Integrated Multitrophic Aquaculture (IMTA) - Joseba Aguilo-Arce; Pere Ferriol; Roberta Trani; Patrizia Puthod; Cataldo Pierri; Caterina Longo (Journal of Marine Science and Engineering, 2023)
The use of marine sponges dates back thousands of years, and interest in these animals is increasing as new applications are discovered. Their potential is extensive, both in their ancient and still popular use as bath sponges for cosmetics and regarding the more recent discovery of bioactive secondary metabolites mainly of interest for the pharmaceutical industry and the less developed aquariology. Despite their proven biofiltration and ecosystem restoration ability and the biomass supply problem for the interested industries, few integrated multi-trophic aquaculture (IMTA) systems incorporate these invertebrates in their facilities. Therefore, in this brief review, the benefits that marine sponges could bring to rapidly growing IMTA systems are summarized, highlighting their suitability for a circular blue economy.